Ameliorative effect of Aegle marmelos leaves extract against cisplatin-induced nephrotoxicity and oxidative stress - Rizwan Ahmad; Mohd. Mujeeb; Aftab Ahmad; Firoz Anwar (Bangladesh Pharmacological Society, 2015)
Withdrawn by the Editor